Innovation in child welfare: Factors affecting adoption of empirically supported interventions. (December 2020) - Agner, Joy; Barile, John P.; Chandler, Susan M.; Berry, Marianne
Highlights: This article examines barriers and supports to innovation and utilization of ESIs in child welfare. Workload and time commitment should be addressed to successfully implement ESIs. Perceived risk of the intervention can prevent caseworkers from utilizing ESIs. Caseworker's social system should be targeted to improve perceived benefit of new interventions. Implementation of ESIs can be enhanced with utilization of Diffusion of Innovation Theory. Abstract: Despite a push to utilize evidence-informed practice there has been little research on unique challenges of implementing empirically supported interventions (ESIs) in child welfare. This study addresses that gap by identifying factors affecting adoption of three ESIs introduced to the child welfare system in Hawai'i: Intensive Home-based Services, Family Wraparound, and Safety, Permanency, and Well-being. In 2015, these programs were initiated as part of a Title IV-E Waiver Demonstration with the intention of preventing unnecessary placements in child welfare and increasing permanency. Two years after their start date, the three programs were utilized at a much lower rate than anticipated. A survey was developed to assess factors affecting program adoption based on data from focus groups and diffusion of innovation theory. Sixty-three caseworkers and unit supervisors were included in the final sample. Logistic regression was used to test relationships between referrals and implementation factors (knowledge, compatibility, relative advantage, risk, workload, time commitment, peer buy-in), and linear regression was used to examine relationships between peer buy-in, peer relationships, and relative advantage. Findings suggest workload, time commitment, and perceived risk of the interventions should be addressed during the implementation of new programs in child welfare, and that the caseworker's social system can be targeted to improve relative advantage of new interventions. This study aims to contribute to knowledge on successful implementation of ESIs in child welfare to improve essential services for children and families.